Discussion on Internal Relations between Liuzijue and Core Stability Training of Lumbar Spine - Guoqing ZHOU; Xinmiao YAO; Hua LI; Qiao LI (康复学报)
Objective:To study the internal relation between Liuzijue of Qigong and core stability training of lumbar spine in principles of rehabilitation medicine.Methods:The basic concepts of respiratory training for abdominal breathing and reverse abdominal breathing were investigated.7 similarities and differences of core concepts and elements between Liuzijue and core stability training were compared through analyzing and summarizing up the breathing of Liuzijue and the activation techniques and mechanisms for local stable muscle between breathing of Liuzijue and core of stability training of lumbar spine.Results:Both Liuzijue and activation training of local stable muscle of lumbar spine were based on reverse abdominal breathing. They can constantly strengthen the ability of the active control of abdominal muscle, diaphragm, pelvic floor muscle and so on. Both Liuzijue and activation training had the same rehabilitation concept. But there were obvious differences in the actual training method and training mode between them, such as Liuzijue was characterized by"guidance and orientation, unify the body and soul", and emphasized the gradual transition from"consciousness strengthening"and"slight attention"to the natural state. However, the activation training of local stable muscle of lumbar spine emphasized on the continuous consciousness enhancement for the training action, and improvement of muscle strength, endurance and coordination capacity.Conclusion:There is a close relationship between Liuzijue and activation training of local stable muscle of lumbar spine in principles of rehabilitation medicine, and both of them can learn from each other. The fact will help to further understand the important role of breathing training and the local stable muscle of lumbar spine in the prevention and treatment of spinal diseases, to provide a more open way for the treatment of chronic lumbago-leg pain.